Factors Affecting English Speaking Performance - Reyes Gadamúz, Adriana Isabel | Prado, Marcia Daniela | Sánchez, Francisco Sánchez Francisco (UNAN, Managua, 2021)
This study analyzes the factors that affect English speaking performance in students of 10th grade at Maestro Gabriel Institute. The sample for the study was 16 students for whom a survey was carried out and the English teacher to whom an interview was applied. Moreover, an observation was used in 3 lessons which were made to observe the practice of the speaking skill; the instruments used in this research were previously validated by experts. To collect the quantitative data the IBM SPSS statistics program was used. The results showed that indeed psychological factors such as anxiety, fear of making mistakes, lack of confidence, lack of motivation and shyness significantly affect the students’ performance when speaking. Furthermore, it was found that deficient rapport between students and the teacher, lack of vocabulary, fluency, practice, participation, interest in the language and pleasant environment are problems that do not allow students to develop the speaking skill. Based on the findings, possible solutions for the teacher were proposed in order to help students to improve this active skill. This public institute needs to have more resources and facilities that the teacher could use to have the students speaking in the lessons